Economic injury levels and sequential sampling plans for Bemisia tabaci (Hemiptera: Aleyrodidae) biotype B on open-field melon crops. (November 2019) - Costa, Thiago L.; Sarmento, Renato A.; Araújo, Tamíris A. de; Pereira, Poliana S.; Silva, Ricardo S.; Lopes, Mayara C.; Picanço, Marcelo C.
Abstract: The sweetpotato whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae), is an important pest in melon crops worldwide. Decision-making systems are an essential part of Integrated Pest Management (IPM) programs and are composed of sampling plans and economic injury levels (EIL). This study aimed to determine the EILs and develop sequential sampling plans for B. tabaci in melon fields at the vegetative and reproductive stages. The EIL for fields at the vegetative and reproductive stages were 0.38 and 0.22 adult of B. tabaci per sample (fifth most apical leaf of the branch). At least 16 and 25 samples were required for the decision-making on melon fields at vegetative and reproductive stages. According to the operating characteristic curves, the probability of making correct control decision using the sequential sampling plans is greater than 90%. In the validation of the sequential sampling plans by the sampling of 64 melon fields, the sequential and conventional plans made similar decisions. The implementation of sequential plans in melon fields at vegetative and reproductive stages reduced 73.05% and 58.38% of the sampling time compared with the conventional sampling plan. The EIL and the sequential sampling plans developed in this study provides adequate, fast and low-cost decision making in melon fields both at the vegetative and reproductive stages. Highlights: Bemisia tabaci reduces the productivity of melon fields by up to 75%. Economic injury level for vegetative stage melon was 0.38 adult per leaf. Economic injury level for reproductive stage melon was 0.22 adult per leaf. Sequential sampling plans for B. tabaci scouting was developed and validated. The sampling plans can be applied to vegetative and reproductive stage melon.